A review on additive manufacturing of sand molds by binder jetting and selective laser sintering. Issue 8 (10th October 2018) - Le Néel, Tugdual Amaury; Mognol, Pascal; Hascoët, Jean-Yves
Abstract : Purpose: The purpose of this paper is to analyze the current state of the art manufacturing techniques using sand molds for the casting industry by the means of additive manufacturing (AM). In particular, this review will cover two families of 3D printing in regards to sand mold fabrication. Design/methodology/approach: This paper will discuss the sand casting manufacturing processes of AM by binder jetting (3D printing) and selective laser sintering. Scientific articles, patents and case studies are analyzed. Topics ranging from the technology types to the economic implications are covered. Findings: The review investigates new factors and methods for mold design, looking at mechanical properties and cost analysis as influenced by material selection, thermal characteristics, topological optimization and manufacturing procedure. Findings in this study suggest that this topic lacks vigorous scientific research and that the case studies by manufacturers thus far are not useful. Research limitations/implications: As demonstrated by the limited data from previous published studies, a more comprehensive and conclusive analysis is needed due to the lack of interest and resources regarding the AM of sand molds. Practical implications: This study is a useful tool for any researchers with an interest in the field of AM of sand molds. Social implications: Key perspectives are proposed. Originality/value: This review highlights current gaps in this field. The review goes beyond the scientific articles by curating patents and professional case studies.